The Effect of Input Pulse on the Soliton Generation in Microresonators - Alhassen, Hawraa; H. A. Sultan (University of Thi-Qar Journal of Science, 2024)
The effect of the input pulse (chirped pulse) on the generation of soliton wave and optical frequency comb in microresonators was studied. The problem was solved numerically using the Lugiato-Lefever equation and the Fourier method by MATLAB program. The effect of Gaussian and ultra-Gaussian pulses, as well as chirped pulses, on the generation of the soliton wave and the frequency comb was also studied. Our study demonstrated that the generation of the soliton and the frequency comb depends on the shape of the pulse intensity distribution. Moreover, the mobility of the soliton and comb changes depending on the shape of the pulse. In addition, the results showed us that the soliton and frequency comb generated in microresonators are strongly affected by the power of the incoming pulse and the radius of the microresonator.